The physical environment of Kongsfjorden–Krossfjorden, an Arctic fjord system in Svalbard - Oddbjørn Bruland; S. Gerland; Agnieszka Beszczynska-Möller; Harald Svendsen; Jon Ove Hagen; Bernard Lefauconnier; Carlo Papucci; Marek Zajaczkowski; Jon Børre Ørbæk; Kai Bischof; Christian Wiencke; Roberto Azzolini; et al. (Polar Research, 2002)
Kongsfjorden-Krossfjorden and the adjacent West Spitsbergen Shelf meet at the common mouth of the two fjord arms. This paper presents our most up-to-date information about the physical environment of this fjord system and identifies important gaps in knowledge. Particular attention is given to the steep physical gradients along the main fjord axis, as well as to seasonal environmental changes. Physical processes on different scales control the large-scale circulation and small-scale (irreversible) mixing of water and its constituents. It is shown that, in addition to the tide, run-off (glacier ablation, snowmelt, summer rainfall and ice calving) and local winds are the main driving forces acting on the upper water masses in the fjord system. The tide is dominated by the semi-diurnal component and the freshwater supply shows a marked seasonal variation pattern and also varies interannually. The wind conditions are characterized by prevailing katabatic winds, which at times are strengthened by the geostrophic wind field over Svalbard. Rotational dynamics have a considerable influence on the circulation patterns within the fjord system and give rise to a strong interaction between the fjord arms. Such dynamics are also the main reason why variations in the shelf water density field, caused by remote forces (tide and coastal winds), propagate as a Kelvin wave into the fjord system. This exchange affects mainly the intermediate and deep water, which is also affected by vertical convection processes driven by cooling of the surface and brine release during ice formation in the inner reaches of the fjord arms. Further aspects covered by this paper include the geological and geomorphological characteristics of the Kongsfjorden area, climate and meteorology, the influence of glaciers, freshwater supply, sea ice conditions, sedimentation processes as well as underwater radiation conditions. The fjord system is assumed to be vulnerable to possible climate changes, and thus is very suitable as a site for the demonstration ...